Considerably enhanced exciton emission of CsPbCl3 perovskite quantum dots by the introduction of potassium and lanthanide ions. Issue 29 (12th July 2018) - Liu, Yanan; Pan, Gencai; Wang, Rong; Shao, He; Wang, He; Xu, Wen; Cui, Haining; Song, Hongwei
Abstract : The photoluminescence quantum yield (PLQY) of blue-violet emission for CsPbCl3 quantum dots (QDs) is still low, which has limited its application in multi-colour displays. Abstract : The photoluminescence quantum yield (PLQY) of blue-violet emission of CsPbCl3 quantum dots (QDs) is still low, which has limited their application in multi-colour displays. It is important to search for efficient perovskite phosphors within this wavelength range. In this work, we first considerably enhanced the photoluminescence quantum yield (PLQY) of the CsPbCl3 QDs from 3.2 to 10.3% by the introduction of potassium ions (K + ). Then, various lanthanide elements (La, Y, Eu, Lu) were further doped into K x Cs1− x PbCl3 QDs. The lanthanide doped K x Cs1− x PbCl3 QDs still demonstrated emissions around 408 nm and the PLQY was further improved to 31%. Finally, we carried out anion exchange by gradually substituting chlorine with bromine. Efficient and tunable emissions ranging from 408–495 nm were obtained, with a maximum PLQY of 90%. This work provides a new approach to improve the efficiency of the blue-violet light of perovskite QDs.